Inventory of Orchid Species and Abiotic Factors in Singkil Swamp Wildlife Sanctuary - Djufri Djufri; Supriatno Supriatno; Rahmiati Rahmiati (Postgraduate, University of Mataram, 2021)
Rawa Singkil Wildlife Sanctuary currently has various threats such as conversion of forest functions to oil palm plantations, encroachment and other deforestation activities, so this has an impact on the loss of original habitat and ecosystems in it, according to Geographic Information System (GIS) data, encroachment on the Singkil Wildlife Reserve area. reached 4,273 ha. This study aims to inventory orchid species and environmental factors. The method used is a descriptive qualitative approach to identify the orchids found. The results of the inventory found 13 species of orchid species from 9 genera consisting of 5 genera of terrestrial orchids, namely Calanthe, Bromheadia, Arudina, Neuwedia and Eulophia. The 4 genera of epiphytic orchids are Dendrobium, Bulbopyhllum, Papilionanthe and Cymbidium. The species Papilionanthe hookeriana (Rchb.f) Schltr is the most dominant orchid with a relative frequency of 21.27% and is classified in the low category B class, while the relative frequency of other orchids ranges from 2.12-17.02% with a very low category. The results of the analysis of environmental conditions pH ranged from 6-6.8, air humidity 75-80%, soil moisture 27-32 and air temperature 27-31 Â°C